Processes of recognizing the commercialization potential of it diploma theses in non-public universities - Bogdan Nogalski; Mariusz Ochla; Cezary Orłowski (Journal of Modern Science)
Objectives The aim of the article is to present the processes of assessing the commercialization potential of diploma theses within the so-called component commercialization.